Synthesis, crystal structures, and mechanochromic properties of bulky trialkylsilylacetylene-substituted aggregation-induced-emission-active 1, 4-dihydropyridine derivatives. (March 2020) - Peng, Jingqing; Liu, Yanze; Wang, Mengzhu; Huang, Shihao; Liu, Miaochang; Zhou, Yunbing; Gao, Wenxia; Huang, Xiaobo; Wu, Huayue
Abstract: Three new D-π-A 1, 4-dihydropyridine compounds (DHP-TMSA, DHP-TBMSA, and DHP-TIPSA ) containing bulky trialkylsilylacetylenes, such as trimethylsilylacetylene (TMSA), tert -butyldimethylsilylacetylene (TBMSA), and triisopropylsilylacetylene (TIPSA), were designed and synthesized. These compounds showed twisted molecular conformations confirmed by the X-ray crystallographic analyses and displayed aggregation-induced emission activities owing to the restriction of intramolecular rotation confirmed by the fluorescence and absorption spectra. Their crystalline structures exhibited orange or yellow fluorescence and could be destroyed by the grinding treatment owing to the looser packing modes, and were all converted to amorphous states. The crystalline-to-amorphous transition in morphology caused the solid-state fluorescence color changes, revealing mechanochromic (MC) properties. Furthermore, the red-shifted MC activities were confirmed to be ascribed to the increased molecular conjugations by the planarization of the molecular conformations. Compared with DHP-TMSA, DHP-TBMSA and DHP-TIPSA were found to exhibit higher contrast MC activities because TBMSA and TIPSA units had larger steric hindrance effect than TMSA unit. This work broadens the structure types of 1, 4-dihydropyridine derivatives compounds and provides new information for the development of new 1, 4-dihydropyridine fluorescent materials containing ethynyl units with excellent solid-state emission stimuli-responsive properties. Graphical abstract: Image 1 Highlights: Three new D-π-A 1, 4-dihydropyridine derivatives containing different trialkylsilylacetylenes were synthesized. These compounds exhibit aggregation-induced emission and mechanochromic properties. The red-shifted mechanochromic activities were ascribed to the planarization of the molecular conformations. The substituents with larger steric hindrance were advantageous to achieve higher contrast mechanochromic activities.